Rise of Police Science and Crime Science in Indonesia: The Police Journals - Gunawan, Hendra; Rahmadsyah Lubis; Nugroho Ari Setyawan (Pusat Penelitian dan Pengembangan Polri, 2024)
Crime science and police science have been well-developed in English-speaking countries, as evidenced in the literature. The two sciences are lacking in discussing Indonesia. This research will reveal crime and police science in Indonesia through the literature review. The method of this study is a narrative review. Articles, books, book chapters, and other grey literature (e.g., public documents) are examined to unearth the rise of crime science and police science in Indonesia. The themes used to investigate crime science and police science in Indonesia are constructed from a global literature review. The study concludes that crime science and police science exist in the literature. Nevertheless, the development is still lacking. This condition is caused by the lack of well-organized institutions facilitating the creation of literature. The police journals operated by the Indonesian National Police (INP/Polri) may become facilitating institutions for enhancing crime science and police science in Indonesia. Similar to the global literature, the development of the sciences is associated with police professionalisation, police education, and police research. Further studies are suggested to explore and assist the development of crime science and police science in Indonesia.